The Relationship Between Academic Stress and Social Support with Emotional Eating among Migrant Students - Dewi Rukmana; Rr. Amanda Pasca Rini; Eko April Ariyanto (Kirana Publisher (KNPub), 2026)
Migrant students face academic demands and complex social dynamics that may increase academic stress and influence eating behavior. Emotional eating refers to food consumption driven by negative emotional states, such as stress and anxiety, rather than physiological needs. This study aimed to examine the relationship between academic stress and social support with emotional eating among migrant students. This research employed a quantitative approach with a correlational design. The participants consisted of 200 migrant students selected using a purposive sampling technique. The research instruments included an Emotional Eating scale adapted from the Dutch Eating Behavior Questionnaire (DEBQ), an academic stress scale based on Lazarus and Folkman's theory (1984), and a social support scale adapted from the Multidimensional Scale of Perceived Social Support (MSPSS). Data were analyzed using multiple regression with IBM SPSS 16.0. The results revealed a highly significant positive simultaneous relationship between academic stress and social support with emotional eating (F = 21.212; p < 0.01; R² = 0.177). Partially, academic stress showed a highly significant positive relationship with emotional eating (t = 4.748; p < 0.01; β = 0.308), and social support also demonstrated a highly significant positive relationship with emotional eating (t = 4.883; p < 0.01; β = 0.317). These findings indicate that in the context of Indonesian migrant students, social support does not always function as a protective factor but may facilitate emotional eating through social eating activities embedded in students' social culture.